2009
DOI: 10.1111/j.1600-0404.1993.tb04142.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial doppler recordings in raised intracranial pressure

Abstract: The pulsatility index (PI) registreted by the transcranial doppler (TCD) was examined in relation to arterial pCO2 (paCO2) and epidural pressure (ICP). In 10 normal subjects PI was studied during variations in paCO2. In 10 neurosurgical patients with head injuries concomitant measurements of PI and ICP were obtained. The results showed a negative exponential correlation between PI and paCO2. PI changed with 3.2% pr mmHg paCO2. A positive exponential correlation between PI and ICP was observed. PI changed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(45 citation statements)
references
References 18 publications
4
38
0
3
Order By: Relevance
“…Below a CPP threshold of 70 mm Hg, a progressive increase was documented in the TCD PI (peak systolic velocity -enddiastolic velocity/mean fl ow velocity). Homburg et al [36] found that the PI changes by 2.4% per 1 mm Hg of ICP.…”
Section: Detection Of Increased Icpmentioning
confidence: 98%
“…Below a CPP threshold of 70 mm Hg, a progressive increase was documented in the TCD PI (peak systolic velocity -enddiastolic velocity/mean fl ow velocity). Homburg et al [36] found that the PI changes by 2.4% per 1 mm Hg of ICP.…”
Section: Detection Of Increased Icpmentioning
confidence: 98%
“…The relation between ICP and PI was estimated by the linear regression equation: ICP = 15.067 + 5.619 x PI, (the increase of (10,16,18,20). It has been demonstrated that waveforms obtained with TCD are affected by both increases of ICP or decreases of CPP.…”
Section: Gura M Et Al: Correlation Of Pulsatility Index With Intracrmentioning
confidence: 99%
“…1,2,14 It has been shown that as ICP rises, typical changes in cerebral blood flow velocities can be measured by TCD. 9,15 Several studies have suggested that TCD-derived end diastolic flow velocity (Vd) and pulsatility index (PI) are useful as noninvasive estimates of ICP in adults with TBI. 7,8,16,19,20,29,30 There are very limited and opposing data on the utility of TCD-derived Vd and PI to noninvasively screen for intracranial hypertension and to follow ICP over time in children with TBI.…”
mentioning
confidence: 99%